Tuning the Structure, Magnetic, and High Frequency Properties of Sc‐Doped Sr0.5Ba0.5ScxFe12‐xO19/NiFe2O4 Hard/Soft Nanocomposites. (31st December 2021) - Almessiere, Munirah A.; Slimani, Yassine; Algarou, Norah A.; Vakhitov, Maksim G.; Klygach, Denis S.; Baykal, Abdulhadi; Zubar, Tatyana I.; Trukhanov, Sergei V.; Trukhanov, Alex V.; Attia, Hussein; Sertkol, Murat; Auwal, İsmail A.
Abstract: The Sr0.5 Ba0.5 Sc x Fe12– x O19 (SrBaSc)/NiFe2 O4 (NiFe) hard–soft nanocomposites (NCs) are synthesized by in situ sol–gel route. Impact of Sc 3+ doping on their structure, morphology, and magnetic properties are examined. X‐ray diﬀraction confirms the coexistence of SrBaSc and NiFe phases without any impurity. Morphology of NCs reveals a cluster of hexagonal plate decorated by spherical grains. Magnetic characteristics of the NCs are examined by using a vibration sample magnetometer at room temperature and 10 K. The x  = 0.000 sample shows some kinks in their M–H loops and the occurrence of two peaks in d M /d H (H). All the NCs with Sc 3+ exhibit smooth shapes of M – H curves with single peak, revealing the complete and perfect exchange coupling behavior. The diverse magnetic parameters at both temperatures are determined. The values of saturation and remanent magnetizations are decreasing with the Sc content increase. The intensive electromagnetic absorption is observed in all the samples. Reﬂection loss (RL) of more than ‐ 18 dB is observed above 3 GHz. Strong coupling between Sc concentration and amplitude–frequency characteristics of the RL can be used for developing of the functional media for high‐frequency devices and will open broad perspectives for practical application in radar‐absorbing technology and electromagnetic compatibility. Abstract : The structure, magnetic, and microwave properties of Sr0.5 Ba0.5 Sc x Fe12– x O19 /NiFe2 O4 ( x  ≤ 0.035) hard/soft nanocomposites synthesized via sol‐gel auto‐combustion method are investigated. Saturation magnetization is enhanced for samples with Sc compared to the non‐doped composite. Exchange coupling effect is the reason for that. The intensive electromagnetic absorption with reflection loss ≈−18 dB is observed in the range of 3–18 GHz.